Framing of Bongani Mafu as Highlanders FC coach in the Chronicle - Tshuma, Sibakhele (Midlands State University, 2020)
Football has become a widely followed „religion‟ just like Christianity. This has influenced a growth of scholarship on the subject from different theoretical positions. This study explores the sport world from a media centric standpoint. It looks at sports, particularly football from the lens of the media. It unearths how the media manufactures reality while at the same time exploring the discourses that prevail in the media with specific reference to football coaches. The study is an exploration of the re-presentation of Bongani Mafu during his tenure as Highlanders FC coach in the Chronicle newspaper in 2015. Grounded in the framing and Foucauldian discourse theory, the study utilizes a qualitative research approach. Purposively selected newspaper articles on Bongani Mafu were subjected to critical discourse and semiotic analysis. Findings suggest that Mafu‟s image and reputation mutates during the study period as upon appointment he was framed as a savior, progressed to be a rabble rouser who cannot deliver and finally a complete failure.